Etamsylate enhances platelet aggregation through G-proteincoupled receptors in patients with macrohematuria following ureteral lithotripsy: a single-center nonrandomized study - E. F. Barinov; D. I. Giller; S. A. Akhundova (Сеченовский вестник)
Aim. To evaluate the effect of etamsylate on the activation of signaling pathways involved in the regulation of platelet aggregation in the setting of macrohematuria following ureteral lithotripsy (ULT).Material and methods. A total of 192 patients undergoing ULT followed by ethamsylate administration were assessed for inclusion in the study. All patients received nonsteroidal anti-inflammatory drugs. The study included 42 patients (20 men and 22 women; mean age 54.2 ± 15.1 years) who developed macrohematuria following administration of three doses of etamsylate (125 mg I.V. the first dose was administered 6 hours after ULT, followed by further doses every 6 hours). Platelet receptor activity was assessed before and after administration of the fourth dose of ethamsylate (125 mg I.V.) using standard (EC50) and subthreshold (EC10) concentrations of agonists: epinephrine, adenosine triphosphate, adenosine diphosphate (ADP), adenosine, platelet-activating factor (PAF), soluble type IV collagen, and a stable thromboxane A2 analog.Results. After administration of the fourth dose of etamsylate, macrohematuria significantly decreased compared to baseline values: 46.6 ± 8.9 vs. 76.7 ± 7.0 red blood cells per field of view (p < 0.001). After administration of the fourth dose of etamsylate, upon stimulation with standard agonist concentrations (EC50), there was a significant increase in the activity of the PAF receptor by 9.1% (p = 0.007), the thromboxane prostanoid receptor by 7.9% (p = 0.006), the glycoprotein VI receptor by 22.8% (p < 0.001), and ethamsylate-induced platelet aggregation by 10.4% (p < 0.05). The maximal aggregatory response using subthreshold agonist concentrations (EC10) was observed when platelets were incubated simultaneously with ethamsylate and ADP: amplitude, slope, and AUC (area under the curve) increased by 16.9%, 60.0%, and 54.7%, respectively, compared to isolated stimulation of P2Y receptors (p < 0.05), and by 26.2%, 77.2%, and 65.6%, respectively, compared to incubation with ethamsylate alone (p < 0.05).Conclusion. The maximal proaggregatory effect of ethamsylate was mediated through P2Y receptors, along with modulation of thromboxane prostanoid and PAF receptors, which promote intracellular Ca²+ elevation